THE GOVERNANCE ROLE OF LABOR UNIONS IN IMPROVING INVESTMENT EFFICIENCY - Shin, Yong-Chul; Tinaikar, Surjit; Zhang, Yu (Indian Journal of Finance and Banking, 2022)
We focus on the role that labor unions can play in influencing firms’ efficiency in corporate investment decisions where investment efficiency is defined as the extent to which deviations from optimal investment levels are minimized. We argue that unions may not simply be adversaries of managements as is often believed but have incentives to monitor managements in ways similar to that of other corporate governance players. These incentives stem from the fact that unions, like other corporate stakeholders, are adversely affected by investment inefficiencies that may result from firm-level overinvestment and underinvestment decisions. Consistent with this explanation, we find that labor unionization is indeed positively associated with improvements in investment efficiency and that these effects are generally stronger in bargaining environments that are favorable to unions. For instance, union effects in improving investment efficiencies are stronger in states where the Democratic Party is more influential and in states which have not enacted legislations that restrict union activities. These results indicate that union monitoring of investment efficiency is more likely to occur through channels that are a part of unions’ collective bargaining processes. Our results are robust to different measures of investment efficiency, different empirical specifications, and endogeneity of union membership.JEL Classification Codes: J51, J59, O16, G31.